Filadelfia duchowieństwa pięciu dekanatów: gnieźnieńskiego (śś. Piotra i Pawła), żnińskiego, łekneńskiego, kcyńskiego i rogowskiego z 1801 r. - Krucki, Łukasz (Archiwa, Biblioteki i Muzea Kościelne, 2014)
In 1801 on the initiative of Andrzej Pesaliński, a parish priest in Juncewo, clergy philadelphia was organized in fi ve deaneries: Gniezno (Sts. Peter and Paul), Żnin, Łekno, Kcynia and Rogów. It was the successor of the earlier confraternities, established in 1743 and including three deaneries: Gniezno (Sts. Peter and Paul), Żnin and Łekno. The basic objectives of the renewed association was to encourage confreres in systematic religious practices, mutual concern and care during illness, and after the death of each of the brothers to celebrate as many Masses as specifi ed by the statute. In addition, each member received a copy of a philadelphia book titled: The inseparable association of fi ve deaneries: Sts. Apostles Peter and Paul Gniezno, Żnin, Łekno, Kcynia and Rogów or close philadelphia of these deaneries(…). Apart from the devotional texts, the book included the list of all members – clergy and laity who resided in the deaneries mentioned in the title. This publication constitutes an important source of information about families of Greater Poland and Pałuki (not only the noble ones), their social position and religious commitment.